Heritage under siege : military implementation of cultural property protection following the 1954 Hague convention - Kila, Joris. (Heritage and Identity, 2012)
Heritage under Siege , winner of the Blue Shield Award 2012, is the result of international multidisciplinary research on the subject of military implementation of cultural property protection (CPP) in the event of conflict. The book considers the practical feasibility as well as ideal perspectives within the juridical boundaries of the 1954 Hague Convention. The situation of today's cultural property protection is discussed. New case studies further introduce and analyze the subject. The results of field research which made it possible to follow and test processes in conflict areas including training, education, international, interagency, and interdisciplinary cooperation are presented here. This book gives a useful overview of the playing field of CPP and its players, as well as contemporary CPP in the context of military tasks during peace keeping and asymmetric operations. It includes suggestions for future directions including possibilities to balance interests and research outcomes as well as military deliverables. A separate section deals with legal aspects.